Study to find factors influencing first tried tobacco use among adolescent students in Bhopal city of Madhya Pradesh, India - Bathma, Vishal; Agarwal, Sanjay; Shukla, Uma (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco use among school children is becoming a serious problem in developing countries. Nearly 8–9 lakh people die every year in India due to diseases related to tobacco use. The present study is done to get information regarding age of first tried and factors that influence this so as to get planning of interventional corrections. Methods:School-based cross-sectional descriptive study was carried out among 2285 Adolescent students in Bhopal city. Data was collected by an anonymous self administered modified Global Youth Tobacco Survey Questionnaire and Data were analyzed by frequency distribution tables, chi square test and univariate logistic regression as required. To explore the age and factors influencing initiation (first tried) of tobacco use among the study population. Results: Amongst all adolescent students 415 (18.2%) ever used the tobacco product in one or other form and 1870 (81.8%) never used the tobacco. Maximum 117 (28.2%) of students initiated tobacco use at the age of 10 years. Most common influencing factors for initiating tobacco use amongst tobacco users was experimentation/curiosity in 229 (55.2%). Conclusions:Most of the ever-users initiated tobacco use at ≤10 years of age. The majorities of them are initiated of tobacco use by curiosity/experiment.